2007
DOI: 10.1158/1535-7163.mct-07-0330
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of an anti–transferrin receptor IgG3-avidin fusion protein with biotinylated saporin results in significant enhancement of its cytotoxicity against malignant hematopoietic cells

Abstract: We have previously developed an antibody fusion protein composed of a mouse/human chimeric IgG3 specific for the human transferrin receptor genetically fused to avidin (anti-hTfR IgG3-Av) as a universal delivery system for cancer therapy. This fusion protein efficiently delivers biotinylated FITC into cancer cells via TfR-mediated endocytosis. In addition, anti-hTfR IgG3-Av alone exhibits intrinsic cytotoxic activity and interferes with hTfR recycling, leading to the rapid degradation of the TfR and lethal iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
67
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 61 publications
(54 reference statements)
9
67
0
Order By: Relevance
“…The presumption that must be made with these types of targeted approaches is that proteins (or other surface molecules) can be identified, which are sufficiently unique in level or pattern of expression to serve as 'specific receptors' for the targeting moiety. In antitumor approaches, for example, numerous constructs have been reported that target transferrin receptor, [39][40][41][42][43][44][45] since this receptor has been reported to be expressed at levels approximately twofold higher in tumors than in normal tissues. 46,47 Intuitively, a twofold difference may not provide a sufficient differential between tumor and normal tissue to confer tumor selectivity, unless the dose-response curve of the therapeutic entity is very steep.…”
mentioning
confidence: 99%
“…The presumption that must be made with these types of targeted approaches is that proteins (or other surface molecules) can be identified, which are sufficiently unique in level or pattern of expression to serve as 'specific receptors' for the targeting moiety. In antitumor approaches, for example, numerous constructs have been reported that target transferrin receptor, [39][40][41][42][43][44][45] since this receptor has been reported to be expressed at levels approximately twofold higher in tumors than in normal tissues. 46,47 Intuitively, a twofold difference may not provide a sufficient differential between tumor and normal tissue to confer tumor selectivity, unless the dose-response curve of the therapeutic entity is very steep.…”
mentioning
confidence: 99%
“…The fascinating multimodal activities of RIPs have since long time generated interest towards developing antitumor drugs that selectively target tumor cells 10 . A stern resolve in this regard, particularly in the case of type 1 RIPs, are the immunotoxins [11][12][13][14][15] , RIPs conjugated to specific antibodies, which may present promising options for treating various diseases and interestingly against HIV-infected cells 16 . The action mechanism of RIPs have been extremely imperceptible and numerous accounts have been put forth to decipher the same.…”
mentioning
confidence: 99%
“…The cells of mammals such as human, mouse, rat, and Chinese hamster serve as hosts for the expression of fusion proteins of biotin-binding proteins and antibodies or other pharmaceutical proteins. [11][12][13][14][15][16][17][18] Given that the codon preferences among these mammals are similar, there is a good chance that mam-tam2A and mam-tam2B would also be highly expressed in the cells of these other mammals. One or two amino acids of mam-tam2A and mam-tam2B could be changed to create derivatives with a lower isoelectric point, 7) reversible biotin-binding capability, 8) or extremely high thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the fusion proteins were expressed in mammalian cells so that the characteristics of the fusion partners, which are quite often mammalian proteins, would be fully retained. [11][12][13][14][15][16][17][18] Monoclonal antibodies against targets such as receptors and surface proteins of cancer cells are popular fusion partners, because these fusion proteins can attach to the cancer cells to deliver the biotinylated therapeutics.…”
mentioning
confidence: 99%